Oralidade e letramento no primeiro ano do ensino fundamental: o gênero discursivo tertúlia em sala de aula - Araújo, Jefferson Santos de (2014)
This work focus on a discourse genre called tertúlia, used in classroom by teacher of first grade students of Ensino Fundamental (Elementary School). Its aim was to promote oral participation after the reading of song lyrics on sessions that occurred between August and November 2010. This study is relevant because oral language is been valued, especially considering the process of teaching and learning to read and write. Theoretically founded on the Psychology of the School of Vigotski and the thinkers influenced by the theory stabout genres of discourse developed by Bakhtin/Voloshinov and through qualitative research methods, we observed tertúlia sessions in a Public School of São Carlos city, São Paulo state, Brazil. Our aim was to analyse, through indiciary paradigm, the tertúlia sessions and also the oral interactions in classroom to verify the possibilities of pedagogical work with oral speech genres articulating oral and written language. By the analysis of audio and video recording of classes and sessions, the interview with the teacher and notes from field of research we concluded the genre tertúlia has potential to motivate oral practices, not the spontaneous, linked to primary speech genres, but near those more complex forms or oral language, linked to writing and, consequently, to secondary speech genres. In what concerns to the process of teaching and learning to read and write, tertúlia, as a speech genre, has contributions to motivating reading and writing.